Multi Phase Center Processing of Ice Sounding Radar Signals for Across Track Surface Clutter Cancellation: Final Report - Nannini, Matteo; Prats, Pau; Scheiber, Rolf; Villano, Michelangelo; Morrison, Keith; Bennett, John; Corr, Hugh (2013)
ESA’s POLarimetric Airborne Radar Ice Sounder demonstrator (POLARIS) – built, maintained and deployed by the Technical University of Denmark (DTU) - operates at P-band and features a multi-phase-center antenna for the purpose of surface clutter suppression. The first data suitable for the development and demonstration of surface clutter cancellation methods were acquired in February 2011 during the IceGrav campaign in Antarctica. The purpose of the present study was to investigate and compare different methods for surface clutter cancellation and to implement a Processing Tool to augment the along-track POLARIS processor developed by ESA, thus improving bedrock detectability. Four algorithms have been selected for implementation and analysis: the standard beamformer, two different clutter nulling algorithms and the optimum beamformer. Prior to the analysis with real POLARIS data the algorithms have been implemented in a simulation environment, allowing for a performance analysis concerning the different input parameters. These included pulse bandwidth, aircraft roll, cross-track terrain slopes, as well as POLARIS antenna patterns. The improved performance of the nulling and optimum beamformer techniques for surface clutter suppression compared to standard beamformer has been demonstrated and requirements on the knowledge of slope and roll parameters have been quantified. By means of simulation it was shown that the relatively large separation of the POLARIS phase centers (~